Intercultural Education in Chile: Colonial Subjectivity and Ethno-Governmental Rationality - Patricio Lepe-Carrión (Universidade de Lisboa, 2016)
This article is the product of research conducted in the frame of FONDECYT Research Initiation project nº 11140804, entitled "Education and Cultural Racism: Evidence and Discursivities in Agents Who Implement the Bilingual Intercultural Education Program (PEIB)", jointly conducted by the University of Chile's Department of Pedagogical Studies and the University of Sao Paulo's Faculty of Education Postdoctoral Program. The text explores the problem of "cultural racism" in intercultural education programs developed for Mapuche indigenous children in Chile. In order to do so, we first examine the production of subjectivity during the colonial era and later the emergence of ethnic issues in the current government agenda. Our evidence and analysis display how the degradation of indigenous peoples is objectified in the Chilean State's discursive practices, perpetuating social and economic inequality through the production and administration of identities, as well as efficiently controlling ethnic conflicts.